2020
DOI: 10.1111/nmo.14027
|View full text |Cite
|
Sign up to set email alerts
|

Association between pain sensitivity and gray matter properties in the sensorimotor network in women with irritable bowel syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…The postcentral gyrus is a key component of sensorimotor network and contributes to the process of visceral stimulation. The cortical thickness of primary somatosensory cortex was associated with pain intensity in female irritable bowel syndrome (IBS) patients ( Grinsvall et al, 2021 ). Previous studies have reported aberrant activity and function of sensorimotor network in functional GI disorders ( Mayer et al, 2009 ; Duan et al, 2021 ; Liu G. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The postcentral gyrus is a key component of sensorimotor network and contributes to the process of visceral stimulation. The cortical thickness of primary somatosensory cortex was associated with pain intensity in female irritable bowel syndrome (IBS) patients ( Grinsvall et al, 2021 ). Previous studies have reported aberrant activity and function of sensorimotor network in functional GI disorders ( Mayer et al, 2009 ; Duan et al, 2021 ; Liu G. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…38 Visceral sensitivity was associated with regional grey matter differences in the sensorimotor network in female patients with IBS, using anatomical measures of structural MRI, which the authors speculated may represent neuroplastic changes. 39 Whereas central sensitisation was common in IBS, this was more pain specific rather than global sensitivity in a questionnaire based study. 40 However, in another study hypersensitive patients with IBS were characterised by increased perception of both pain and non-painful sensations.…”
Section: Painementioning
confidence: 92%
“…The work in this article have been carried out in accordance with The Code of Ethics of the World Medical Association (Declaration of Helsinki). This study population has also been used to study resting state fMRI connectivity [30], and associations between regional gray matter metrics with visceral sensitivity measures [31].…”
Section: Subjectsmentioning
confidence: 99%